Modelling adaptive systems with nets-within-nets in maude - Lorenzo Capra and Michael Köhler-Bußmeier (SciTePress, 2023)
Systems able to dynamically adapt their behaviour gain growing attention to raising service quality by reduc- ing development costs. On the other hand, adaptation is a major source of complexity and calls for suitable methodologies during the whole system life cycle. A challenging point is the system’s structural reconfigu- ration in front of particular events like component failure/congestion. This solution is so common in modern distributed systems that it has led to defining ad-hoc extensions of known formal models (e.g., the pi-calculus) But even with syntactic sugar, these formalisms differ enough from daily programming languages. This work aims to bridge the gap between theory and practice by introducing an abstract machine for the “nets-within- nets” paradigm. Our encoding is in the well-known Maude language, whose rewriting logic semantics ensures the mathematical soundness needed for analysis and an intuitive operational perspective.
Keywords: Adaptive Systems; Maude; Nets-Within-Nets